Green Organizing in Austin, Texas: Place-ballet and the rhetorical community, 1990-1999 - Hirsh, Curtis (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2002)
AbstractThis article addresses the organizational and discursive dynamics of a green urban movement in Austin, Texas, and how one community found its voice and translated a significant current of opinion into an effective cultural and political force. Of particular interest is the production and deployment of assorted texts and cultural capital by environmental activists in full engagement with a no less determined multinational corporation. The objects and artifacts, as we observe them during a flânerie or “walkabout” of the town’s symbolic center, provide a rich interpretive source for understanding the culture and community which produced them.